2022
DOI: 10.1007/s10578-022-01348-1
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 pandemic and its impact on tic symptoms in children and young people: a prospective cohort study

Abstract: To understand how children and young people with tic disorders were affected by COVID-19, we compared pre and during pandemic scores on the Yale Global Tic Severity Scale (YGTSS). Participants were young people (N = 112; male:78%; 9–17 years) randomised to the control arm of the “ORBIT-Trial” (ISRCTN70758207, ClinicalTrials.gov-NCT03483493). For this analysis, the control arm was split into two groups: one group was followed up to 12-months’ post-randomisation before the pandemic started (pre-COVID group, n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“… 17 The largest UK tic study utilising pre- and during pandemic tic scores followed 112 (78% male) children with tics who participated in the active control group of a randomised controlled trial (“ORBIT Trial”). 18 , 19 The analysis revealed no difference in tic severity during the pandemic, 20 although the sample was limited to children who were diagnosed with a tic disorder pre-pandemic. Taken together, these findings indicate a mixed, complex picture in which some groups of children and young people may be differentially at greater risk than others of developing tics during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 92%
“… 17 The largest UK tic study utilising pre- and during pandemic tic scores followed 112 (78% male) children with tics who participated in the active control group of a randomised controlled trial (“ORBIT Trial”). 18 , 19 The analysis revealed no difference in tic severity during the pandemic, 20 although the sample was limited to children who were diagnosed with a tic disorder pre-pandemic. Taken together, these findings indicate a mixed, complex picture in which some groups of children and young people may be differentially at greater risk than others of developing tics during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 92%
“…However, the impact of the pandemic on tic severity in adolescents with Tourette Syndrome (TS), and whether impacts are sex specific, is unclear. Previous reports regarding the impact of the pandemic on tic severity from male predominant cohorts that were inclusive of children over a broad age range have been conflicting, with some reporting worsening (5), improvement (6), or no difference (7). A female predominant adult cohort reported 48% of respondents perceived worsening of tics during the pandemic, while 44% reported no change in tic severity (8).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports regarding the impact of the pandemic on tic severity from male-predominant cohorts that were inclusive of children over a broad age range have been conflicting, with some reporting worsening, 5 improvement, 6 or no difference. 7 A female-predominant adult cohort reported that 48% of respondents perceived worsening of tics during the pandemic, while 44% reported no change in tic severity. 8 Additionally, girls have comprised over 90% of functional tic-like behaviors that have dramatically increased during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The result was not influenced by age or gender or by symptoms of anxiety or ASD. From this, we concluded that COVID‐19 did not significantly impact tics in our sample of children and young people who already had an existing tic disorder (Hall et al., 2022).…”
Section: Discussionmentioning
confidence: 70%